BREAKING THE OBSTACLES: ENGLISH SPEAKING DIFFICULTIES FACED BY CADETS AT A MARINE INSTITUTE - Dhinar Sari (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2025)
English-speaking competence is essential for maritime cadets, as effective communication plays a critical role in safety, navigation, and professional interaction in international maritime contexts. Despite having received formal instruction in Maritime English, many cadets still find it difficult to use English confidently and effectively when speaking. This study examines the challenges faced by Indonesian maritime cadets in speaking English and the factors that influence them in the context of EFL. This study used an exploratory qualitative case study design approach involving three cadets from a maritime institution in Indonesia who had different levels of English proficiency, namely basic, intermediate, and advanced, to allow for in-depth exploration of speaking difficulties across proficiency levels. Data were collected through semi-structured interviews and classroom observations. Subsequently, the data were analyzed using thematic analysis based on Braun and Clarke’s framework. The study results indicate that cadets face various linguistic difficulties, such as limited vocabulary, pronunciation errors, and weak grammar skills. Non-linguistic factors, such as nervousness when talking, lack of motivation, fear of making mistakes, lack of practice opportunities, and the use of the native language, also influence oral skills. These factors result in some cadets limiting their use of English to only the classroom and even that ​‍​‌‍​‍‌occasionally. The study highlights the significance of establishing supportive and communicative learning atmospheres. These are the places where students are prompted to speak regularly in class, become less anxious, and simultaneously, their fluency and accuracy are balanced. The results contribute to the teaching practices of ESP, particularly maritime English, by emphasizing the necessity of context-sensitive and communicative teaching approaches to better prepare cadets for authentic maritime communication